Acute Functional Outcomes in Critically Ill COVID-19 Patients - Tay, Matthew Rong Jie; Ong, Poo Lee; Puah, Ser Hon; Tham, Shuen Loong (Frontiers in Medicine, 2021)
Background: COVID-19 (Coronavirus Disease 2019) is a global cause of morbidity and mortality currently. We aim to describe the acute functional outcomes of critically ill coronavirus disease 2019 (COVID-19) patients after transferring out of the intensive care unit (ICU). Methods: 51 consecutive critically ill COVID-19 patients at a national designated center for COVID-19 were included in this exploratory, retrospective observational cohort study from January 1 to May 31, 2020. Demographic and clinical data were collected and analyzed. Functional outcomes were measured primarily with the Functional Ambulation Category (FAC), and divided into 2 categories: dependent ambulators (FAC 0-3) and independent ambulators (FAC 4-5). Multivariate analysis was performed to determine associations. Results: Many patients were dependent ambulators (47.1%) upon transferring out of ICU, although 92.2% regained independent ambulation at discharge. On multivariate analysis, we found that a Charlson Comorbidity Index of 1 or more (odds ratio 14.02, 95% CI 1.15-171.28, P=0.039) and a longer length of ICU stay (odds ratio 1.50, 95% CI 1.04-2.16, P=0.029) were associated with dependent ambulation upon discharge from ICU. Conclusions: Critically ill COVID-19 survivors have a high level of impairment following discharge from ICU. Such patients should be screened for impairment and managed appropriately by rehabilitation professionals, so as to achieve good functional outcomes on discharge.